(untitled) (Annals of Medical Research, 2021)
Aim: This study was designed to compare rates of acute HAV infection and HAV seroprevalence in patients aged 0-6 years and 7-15 years in a pediatric hospital before and after the HAV vaccine was added to the national immunization program in 2012.Material and Methods: A total of 16,917 serum samples were evaluated in the study. Sera of the 5520 patients (3,208 of 0-6 years, 2,312 of 7-15 years) were collected during 2011 and analyzed for anti-HAV IgM and anti-HAV IgG with chemiluminescent assay (period 1). After that a total of 11,397 sera of the patients (5,473 of 0-6 years and 5,924 of 7-15 years) were collected between 1 July 2014 and 31 December 2016 and analyzed for anti-HAV IgM and anti-HAV total (period 2).Results: In period 1, rates of acute HAV infection and seropositivity were 26.87% and 19.25% in the 0-6 years , and 42.39% and 41.52% in the 7-15 years. Prior to routine vaccination, 54.03% of patients in the 0-6 age group and 16.08% of patients in the 7-15 age groups were susceptible to HAV infection.In period 2, Anti-HAV IgM positivity rates in 2014, 2015, and 2016 were 14.06%, 3.92%, and 2.46% in the 0-6 age group and 16.85%, 6.80%, and 4.48% in the 7-15 age group, respectively. Seropositivity rates were 43.66%, 59.55%, and 66.09% in the 0-6 age group and 45.67%, 55.41%, and 54.04% in the 7-15 age group, respectively. After routine vaccination, rates of children who were susceptible to HAV infection decreased from 42.28% and 36.52 % to 31.45% in the 0-6 years and increased from 37.48%, 37.79% to 41.48% in the 7-15 years. Considering the data as a whole, the most striking finding was that the acute infection rate in the 0-6 years was decreased firstly by 47.67% and then by 85.42% and 90.85% compared to the pre-vaccination period. However, a progressive decline was also observed in the 7-15 years compared to the pre-vaccination period; the rate decreased by 60.25%, 83.96%, and 89.43%, respectively in period 2. This fall in infection rates among a non-target group of HAV vaccination can be attributed to the effect of the vaccine on "herd immunity".Conclusion: Adding HAV vaccine to the routine immunization program effectively reduced rates of acute infection, demonstrating the contribution of vaccination to herd immunity. Studies showing the efficacy of vaccination programs are essential for raising public awareness.